Surgical management of the aortic arch in patients with inherited aortopathy - Lucchese, Gianluca; Bilkhu, Rajdeep (Frontiers in Cardiovascular Medicine, 2022)
Surgical management of the aortic root and ascending aorta has seen an evolution over the past 50 years. Despite the widely available guidelines for management of the aortic root and ascending aorta, including in those with connective tissue disease and inherited aortopathies, there are generally no clear guideline indications for when to intervene on the aortic arch in these patients. This perhaps may be related to the fact that whilst the majority of acquired aortopathies, and also in non-syndromic aortopathies such as in bicuspid aortic valve, size criteria are utilized to decide on when to intervene, the use of size criteria may not be appropriate in those with syndromic inherited aortopathies. The aim of the present mini review is to provide a general overview and guidance for the surgical management of patients with inherited aortopathies.